How to Treat a Child With a Concurrent Diagnosis of Leukemia and Generalized Mucormycosis? Case Report - Sosnowska-Sienkiewicz, Patrycja; Błaszczyk, Kinga; Kubisiak-Rzepczyk, Honorata; Mańkowski, Przemysław; Januszkiewicz-Lewandowska, Danuta (Frontiers in Medicine, 2022)
Mucormycosis is a rare but a devastating and lifethreatening fungal infection caused by fungi of the order Mucorales usually in immunocompromised patients. Depending on the organs and tissues involved, there are sinus, pulmonary, gastrointestinal, orbital, cerebral, cutaneous and disseminated mucormycosis. Only sporadic cases of hepatic mucormycosis have been described. Hence, we present a complicated treatment management in a 16-month-old child with leukemia and generalized mucormycosis localized in the liver and in the gastrointestinal tract. The collaboration of a multidisciplinary team and appropriate therapy gave a chance not only to save the patient's life, but to carry out anticancer treatment, which resulted in leukemia remission. A 6-month course of isavuconazole and amphotericin B liposomal as well as surgical treatment led to the cure of the fungal infection.